2017
DOI: 10.1016/j.heliyon.2017.e00462
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps militaris improves the survival of Dahl salt-sensitive hypertensive rats possibly via influences of mitochondria and autophagy functions

Abstract: The genus Cordyceps and its specific ingredient, cordycepin, have attracted much attention for multiple health benefits and expectations for lifespan extension. We analyzed whether Cordyceps militaris (CM), which contains large amounts of cordycepin, can extend the survival of Dahl salt-sensitive rats, whose survival was reduced to ∼3 months via a high-salt diet. The survival of these life-shortened rats was extended significantly when supplemented with CM, possibly due to a minimization of the effects of stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In fact, ample evidence has shown the role of Sirt3 in mitochondrial homeostasis and ROS management. For example, Sirt3 is associated with mitochondrial cardiolipin expression (Chabi et al 2018), mPTP opening regulation (Nassir et al 2018), mitochondrial energy production (Wu et al 2018), autophagy activity (Takakura et al 2017), cellular oxidative stress (Lee et al 2018), and metabolic reprogramming (Lee et al 2017a). More importantly, the protective effects of Sirt3 on mitochondria have been verified in different disease models, including Alzheimer's disease (Lee et al 2018), gastric cancer (Lee et al 2017a), fatty liver disease (Liu et al 2017a), and heart failure (Du et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, ample evidence has shown the role of Sirt3 in mitochondrial homeostasis and ROS management. For example, Sirt3 is associated with mitochondrial cardiolipin expression (Chabi et al 2018), mPTP opening regulation (Nassir et al 2018), mitochondrial energy production (Wu et al 2018), autophagy activity (Takakura et al 2017), cellular oxidative stress (Lee et al 2018), and metabolic reprogramming (Lee et al 2017a). More importantly, the protective effects of Sirt3 on mitochondria have been verified in different disease models, including Alzheimer's disease (Lee et al 2018), gastric cancer (Lee et al 2017a), fatty liver disease (Liu et al 2017a), and heart failure (Du et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is recapitulated in salt-sensitive rats that are fed via a high-salt diet, where cordycepin-induced autophagy is associated with lifespan extension and protection of hypertension-sensitive organs, including the brain, heart, kidney, and liver [ 228 ]. Morphologically, neurons, cardiomyocytes, glomerular podocytes, renal epithelial cells, and hepatocytes are all improved in cordycepin-treated rats featuring reduced levels of AKT/mTOR, increased levels of AMPK, and decreased levels of p62 witnessing for autophagy flux progression, as compared to the untreated controls [ 228 ]. A cordycepin derivative, through AMPK activation, also alleviates atherosclerosis in High-Fat Diet-Fed ApoE-KO mice, by protecting the vascular endothelial cells from inflammatory and oxidative damage [ 229 ].…”
Section: Anti-viral and Anti-inflammatory Effects Of Phytochemicalmentioning
confidence: 99%
“…Our past research has found that in the process of liquid culture of C. militaris, different fermentation substrates not only affect the yields of biomass production (including extracellular polysaccharides, cordycepin, and mycelium production), but also affect the activity of suppressing oral cancer [6]. In addition to cancer suppression, C. militaris also has the potential to improve metabolic syndrome, including diabetes [7], hypertension blood pressure [8], and hyperlipidemia [9]. There are more than 1000 different microbial species (species) in the human gastrointestinal (GI) tract; these bacterial phases constitute a specific microenvironment in the gut.…”
Section: Introductionmentioning
confidence: 99%